2016
DOI: 10.4103/0366-6999.190677
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of the Molecular Pathways in Fibrosis Induced by MicroRNAs

Abstract: Objective:MicroRNAs (miRNAs or miRs) play critical roles in the fibrotic process in different organs. We summarized the latest research progress on the roles and mechanisms of miRNAs in the regulation of the molecular signaling pathways involved in fibrosis.Data Sources:Papers published in English from January 2010 to August 2015 were selected from the PubMed and Web of Science databases using the search terms “microRNA”, “miR”, “transforming growth factor β”, “tgf β”, “mitogen-activated protein kinase”, “mapk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 73 publications
0
34
0
1
Order By: Relevance
“…miRNAs miR-27a-3p promotes the malignant phenotypes of osteosarcoma by targeting ten-eleven translocation 1 regulate gene expression via the specific binding to target genes (23). Over the past decades, a large number of miRNAs have been identified and are believed to play an important role in the occurrence, differentiation, proliferation and apoptosis of cells (24,25). Recent studies have indicated that alterations in miRNA expression are associated with the occurrence, development, diagnosis and prognosis of cancers (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs miR-27a-3p promotes the malignant phenotypes of osteosarcoma by targeting ten-eleven translocation 1 regulate gene expression via the specific binding to target genes (23). Over the past decades, a large number of miRNAs have been identified and are believed to play an important role in the occurrence, differentiation, proliferation and apoptosis of cells (24,25). Recent studies have indicated that alterations in miRNA expression are associated with the occurrence, development, diagnosis and prognosis of cancers (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Makino and co-workers reported that depletion of miRNA-196a level in 3 localized scleroderma skin biopsies was statistically significant compared with 3 keloid skin samples and 3 normal skin biopsies [18]. Consistent with knockdown of microRNA-196a in LoSc skin, the serum concentrations of miRNA-196a were remarkably diminished in patients with localized scleroderma (34) in contrast to healthy controls (22) [18].…”
Section: Mirna-196amentioning
confidence: 81%
“…Recent reports have shown that several microRNAs participate in regulation of processes that drive fibrosis, including transforming growth factor (TGF-β) signalling, fibroblast proliferation and differentiation, extracellular matrix proteins deposition and epithelial-to-mesenchymal transition (EMT) [3,18,34]. Upregulation of some profibrotic micro-RNAs results in fibrosis, whereas antifibrotic miRNAs suppress this process and may be knock-down in fibrosis [13].…”
Section: Microrna and Fibrosismentioning
confidence: 99%
“…Particular classes of miRNAs have been identified as strong regulators of fibrotic processes, namely “fibromiRs” and “redoximiRs,” effective genetic regulators of ROS generation (87, 88). Furthermore, miRNAs have also been found to influence various pathways comprising TGF-β, SMADs, and other extracellular matrix (ECM) proteins that are predominantly influential to both universal and organ-specific fibrogenesis (89, 90). …”
Section: Potential Targets For Mitigation and Treatment Of Fibrosismentioning
confidence: 99%